DESCRIPTION OF LEXICAL UNITS ON THE ORGANIZATION OF EDUCATION IN UZBEKISTAN AND GERMANY (Scientific journal of the Fergana State University, 2024)
The process of globalization taking place in the world is the reason for intensive exchange of information and establishment of close relations between different countries. Especially, this process is of particular importance in the field of education, which creates the need to translate textbooks, scientific articles, conference materials and other scientific resources into different languages. Participation in the exchange of academic programs, mutual cooperation between universities and research centers of different countries is expanding. From this point of view, the comparative study of the vocabulary of the educational system of Germany and Uzbekistan is important for cooperation in this field.As a result of the continuous development in the field of education in the countries of the world, the introduction of new technologies into practice, the use of modern methods and approaches, it is required to understand the vocabulary of the relevant field. A comparative study of lexical units related to the educational system in the Uzbek and German languages ​​reveals the uniqueness, similarities and differences in the use of new terms, concepts and approaches, as well as their compliance with national educational standards. Increasing attention to the development of the education system in our country has become a priority task of the reforms implemented by the head of state. A number of decisions and orders have been developed regarding the study and implementation of advanced experiences in the educational system of developed foreign countries. Therefore, one of the urgent problems is to thoroughly study and analyze the specific features of the educational system of the Federal Republic of Germany, which is recognized as a developed country by the world, which is far from each other, and to introduce the achieved achievements into the educational system of our country.Therefore, "We consider it our priority to strengthen good neighborly and friendly relations with all the countries of the world". Decision PQ-1875 on "Further improvement of teaching of foreign languages" adopted by the first President of the Republic of Uzbekistan on December 10, 2012, the development of all areas in our country requires the knowledge and skills of the specialists working in foreign languages. and this, in turn, became the basis for large-scale research on English, German and French languages.